"If Luther will accept us with our confession …": The Eucharistic controversy in Calvin"s correspondence up to 1546 - Heron, Alasdair I. C. (HTS teologiese studies, 2006)
The article explores Calvin's attitude to the Eucharistic controversy between Wittenberg and Zurich in the years up till Luther's death in 1546. The main source is Calvin’s letters from that period, which cast a differentiated light on his aims, hopes and disappointments on the question as well as on his relations to other leading Reformers. Account is also taken of several recent publications, which suggest revision of some long-standing views in Calvin scholarship.